The Use of Learning Media on the Speaking Subject of Islamic Higher Educations in The Entire Central Java and Yogyakarta - Faizah, Umi; Suwandi, Sarwiji; Andayani; Rahmawati, A (Journal of physics. Conference series, 2019)
This research aims at describing (1) the use of learning media on the speaking subject; (2) the opportunity of Islamic mission rhetoric learning media based on scientific approach on the speaking subject. The settings of this research are at Purworejo Muhammadiyah University, Purwokerto Muhammadiyah University, Surakarta Muhammadiyah University, and Yogyakarta Ahmad Dahlan University. Method of this research is a descriptive-qualitative one, namely by describing the findings found in the field obtaining through observation, interview, and questionnaire. Sample of the research consists of 247 students and 4 lecturers. The results of this research are (1) the media used on the speaking subject, among others, are rainbow kicir, doraemon pocket, telling earth, puzzle, doll, puppet, youTube, hand phone, and lap top to support the students speaking competency; (2) there is an opportunity to use Islamic mission rhetoric learning media based on scientific approach because the use of audio-visual media has not been utilized optimally, i.e. the approach and media have not been integrated.